Identification of nuclear export signal in KLLN suggests potential role in proteasomal degradation in cancer cells - Sankunny, Madhav (Oncotarget, 2020)
Germline and somatic promoter hypermethylation of KLLN has been found in diverse heritable and sporadic cancers, respectively. KLLN has many identified tumor suppressor functions, and when first reported, was thought to be exclusively nuclear. Here, we report on KLLN localization in both the nucleus and cytoplasm and the identification of a putative nuclear export signal (NES) sequence. KLLN overexpression in colon and breast cancer cells showed both nuclear and cytoplasmic presence. Inhibition of the CRM1 export pathway increased nuclear sequestration of KLLN, confirming the prediction of an NES sequence. Point mutations introduced in the predicted NES sequence decreased the strength of the NES and increased the nuclear sequestration of KLLN. Contrary to expectations, the transcription regulation and cellular proliferation functions of KLLN were unaffected by increased KLLN nuclear sequestration. Instead, increased nuclear KLLN correlated with increased nuclear sequestration of TRIM25 and decreased inhibitory phosphorylation of MDM2. Computational analysis of The Cancer Genome Atlas (TCGA) dataset showed positive correlation among KLLN, TRIM25 and MDM2 expression; pathway analysis of the common genes downstream of these three genes revealed protein degradation as one of the top canonical pathways. Together, our observations suggest that CRM1 pathway-based nuclear export of KLLN may impact proteasomal degradation.